Upaya Orangtua dalam Mengatasi Ketergantungan HP Android pada Anak-anak di Desa Kaweron Kecamatan Talun Kabupaten Blitar - Sulailiya Sulailiya; Wikan Galuh Widyarto (Universitas Negeri Makassar, 2021)
This study aims to describe the impacts of android cellphone dependence on children, describing parents' efforts in overcoming android cellphone dependence on children, and describing the response in children to the efforts given by their parents. In this research, in Kaweron Village, District, there are two children who are key informants, while supporting informants such as private academic tutors, private Koran tutors and siblings of one of the informants and parents. The data were collected by using observation, interview, and documentation methods called data triangulation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions and verification. Research findings show that children's dependence on android phones, such as staying up late playing online or offline games until late at night, makes eyes tired, feels worried if one day doesn't hold an android phone and sometimes sweats palms.